Assessment of preschool‐age executive functions: A systematic review. (9th February 2022) - Silva, Cristina; Sousa‐Gomes, Valéria; Fávero, Marisalva; Oliveira‐Lopes, Susana; Merendeiro, Cristiana S.; Oliveira, Jorge; Moreira, Diana
Abstract: Executive functions (EF) are higher‐order cognitive processes present in the prefrontal cortex and are fundamental in planning, executing and monitoring goal‐oriented behaviours. Evaluating EF in early stages of child development is essential for identifying any cognitive alterations in young children, given that it allows for early intervention and minimizes future complications. Additionally, it contributes to a better understanding of this construct in this age bracket, as well as its operational model. Study of EF has recently been the focus of multiple researchers; however, there is still a serious lack of instruments and measurements validated towards children's age bracket. This systematic review's main goal is to evaluate instruments and/or tasks that serve to evaluate and analyse EF and/or their components between the ages of 36 and 72 months. Forty‐nine studies were analysed, containing multiple tasks and tools oriented towards EF and their constituent components. Results indicate the existence of various tasks that grade the different components independently from one another; nevertheless, they also confirm the lack of any global measurement instrument or method. Therefore, this systematic review presents itself as an important contribution in the study of EF, stressing not only the importance of further investing into constructing and validating new and better tools for evaluating the construct but also the study of operating models of executive functioning, especially in an age bracket where comprehending it is notoriously difficult.